Inflection of Nouns in the Lokal Dialect of the Village of Berezno, Kholm Province (Plural noun Forms) (Linguostylistic Studies, 2015)
The article discusses morphological peculiarities (singular noun forms) in the speech of the residents of the village of Berezno, Kholm province. Morphological system Kholm lokal dialects is extremely interesting and requires a thorough study in view of the fact that it is not specifically examined. The analysis reveals both common features and differences with other lokal dialects of south-western vernacular of the Ukrainian language. A significant number of morphological phenomena are related to phonological system of the Kholm lokal dialects (-е instead of ending -и in an accented position, implementation of the ancient гы, кы, хы as гі, кі, хі in an unaccented position and as гє, кє, хє in an accented position etc.). The Kholm lokal dialects have maintained many archaic linguistic features: the remains of the dual nouns, active functioning uncontracted full forms of adjectives, verbal infinitive form on -чи, the remains of ancient forms of perfect and others. Key words: Berezno, Kholm province, lokal dialect, noun, morphology. References